Global drivers of Russian timber harvest - Liang, Sai (Animo Repository, 2016)
Russian forest resources are important for global carbon cycling. In contrast to traditional analyses that focus on the harvest and direct use of Russian timber resources (a.k.a. production-based accounting), this study investigates how the consumption of nations drives Russian timber harvest (a.k.a. consumption-based accounting or the Russian timber footprint). China is the biggest direct importer and final consumer of Russian timber. The United States, Japan, and major European countries directly import relatively small amounts of Russian timber, but serve to drive large amounts of Russian timber harvest through their final consumption. Through structural path analysis, individual supply chain paths are delineated to show linkages between Russian timber harvest and the final consumption of nations. Findings of this study inform consumption-side measures for Russian forest conservation, for example, taking shared responsibility and improving the production efficiency of key sectors in consuming nations. © 2016 by Yale University